When Similarity Becomes Opposition: Synonyms and Antonyms Discrimination in DSMs - Enrico Santus; Qin Lu; Alessandro Lenci; Chu-Ren Huang (IJCoL)
This paper analyzes the concept of opposition and describes a fully unsupervised method for its automatic discrimination from near-synonymy in Distributional Semantic Models (DSMs). The discriminating method is based on the hypothesis that, even though both near-synonyms and opposites are mostly distributionally similar, opposites are different from each other in at least one dimension of meaning, which can be assumed to be salient. Such hypothesis has been implemented in APAnt, a distributional measure that evaluates the extent of the intersection among the most relevant contexts of two words (where relevance is measured as mutual dependency), and its saliency (i.e. their average rank in the mutual dependency sorted list of contexts). The measure – previously introduced in some pilot studies – is presented here with two variants. Evaluation shows that it outperforms three baselines in an antonym retrieval task: the vector cosine, a baseline implementing the co-occurrence hypothesis, and a random rank. This paper describes the algorithm in details and analyzes its current limitations, suggesting that extensions may be developed for discriminating antonyms not only from near-synonyms but also from other semantic relations. During the evaluation, we have noticed that APAnt also has a particular preference for hypernyms.